CuO as a reactive and reusable reagent for the hydrogenation of nitroarenes - Rajendran, K.; Pandurangan, N.; Vinod, C. P.; Khan, Tuhin S.; Gupta, Shelaka; Haider, M. Ali; Jagadeesan, D. (Applied Catalysis B-Environmental, 2021)
{Copper oxide (CuO) is used as a reusable solid reagent for hydrogenation of nitroarenes to aminoarenes. The use of CuO resulted in 100 % conversion of 2.9 mmol of nitrobenzene to aniline in 45 s at room temperature using hydrazine hydrate as the reducing agent. During the reaction, CuO is converted to inactive metallic Cu which can be regenerated to active CuO by thermal oxidation. DFT simulations indicated facile formation of oxygen vacancies (EO
Keywords: Copper vacancy; CuO; Hydrogenation; Nitroarene reduction; Oxygen defects; Reactive solids